Urban pastoralism as green infrastructure generator that provides important ecosystem services to the city - Triboi R.M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Pastoralism is a pattern of subsistence, that has survived in its close to original form even today in an increasingly urbanized environment. Marginalized by agriculture intensification, then industrialization and lately by the urbanization processes, this productive practice was restrained to marginal spaces and interstice of urban territory unexploitable by other activities. Its capacity of adaptation to harsh and changing conditions generated its resilience. The interdependency between the exploited environment, the shepherd and the flock along with the independence from urban infrastructure and mechanization permitted its survival despite its criticized low productivity, while transforming marginal land in productive and biodiverse spaces. Historically ignored by policies, a reconsideration of this practice is necessary, especially in the urban environment. In Romania, due to a combination of factors like rapid fragmentation of the rural and agricultural city’s periphery by the urban sprawl phenomenon or the abandonment of agricultural exploitation of ancient socialist farm land located in the immediate proximity of the cities, the phenomenon of urban pastoralism developed in the last 2 decades in the urban interstices of nature. In France, the last decade has seen the evolution of eco-pastoralism in the city from experimenttion to institutionalization for ecological management of urban green spaces. While traditionally perceived as a rural practice, the pastoralism values the social, cultural, economic, ecological and agricultural dimensions of urban territories; with an appropriate recognition and management it could become an important tool for sustainable urban management. Its important role in supporting green infrastructure and local food systems is yet to be considered and integrated into urban policies.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)